ENVIRONMENT CONSERVATION ACT AND OTHER RELATED ACTS - Suvarna, K. (International Journal of Research -GRANTHAALAYAH, 2015)
Environment is derived from the French word Environner, which means to encircle or surround. All the biological and non-biological entities surrounding us are included in environment. Environment is one subject that is actually global as well as local in nature. Issues like global biodiversity etc. which are going to affect the mankind as a whole are global in nature and for that we have to think and plan globally.